Penerapan Prinsip Tanggung Jawab Negara terhadap Pengelolaan Kawasan Ekosistem Leuser di Aceh - Fikri Fikri (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: The international society considers the existence of forest has  close relation to biodiversity and climate changing problems. Therefore, the countries are required to manage forest  prevent it from causing a damage or pollution direct or indirectly to the environment in national territory or beyond the limit of national jurisdiction. Indonesiahas been implementing this principles in state obligation to harmonize the policy and national regulations according to the international agreements in the realization to suistainable forest management. For this purpose, the government has made some provisions related to forest such Undang-undang No. 41 in 1999 concerning foresrtry. For the Leuser forest in Nanggroe Aceh Darussalam Province has somes provisions on suistainable forest management such as in Intruksi Gubernur No.5/Instr/2007 relating to Moratorium Logging. Those provisions show the commitment of Indonesia in performing the international responsiblility on suistainable forest management. The Application of State’s Responsibility Principle on the Management of Leuser Ecosystem Territory in Aceh